Analysis of the Variability of Therapeutic Indications of Medicinal Species in the Northeast of Brazil: Comparative Study. (23rd April 2018) - Ferreira Macedo, Julimery Gonçalves; Menezes, Irwin Rose Alencar de; Alves Ribeiro, Daiany; de Oliveira Santos, Maria; Gonçalves de Mâcedo, Delmacia; Ferreira Macêdo, Márcia Jordana; Vilar de Almeida, Bianca; Souza de Oliveira, Liana Geraldo; Pereira Leite, Catarina; de Almeida Souza, Marta Maria
Abstract : Ethnopharmacological Relevance . This study aims to evaluate the versatility of these species and their agreement of use and/or the informants' knowledge and verify the variability of the information on the indicated medicinal species in comparison to other species from northeastern Brazilian areas. Materials and Methods . Ethnobotanical information was acquired through interviews with 23 residents of the Quincuncá community, northeastern Brazil. From the obtained data, a comparative analysis of the therapeutic indications with other 40 areas in different biomes was conducted. For that, the relative importance index and informant consensus factor were calculated and compared to other indices evaluated in the literature. Results. A total of 39 medicinal species were cited and twenty-six species showed similarities among their therapeutic indications; however, species as Geoffroea spinosa, Lantana camara, and others can be highlighted, present in community disease indications that were not verified for other areas. Myracrodruon urundeuva, Mimosa tenuiflora, Stryphnodendron rotundifolium, and Amburana cearensis had the greatest versatility. In the Quincuncá community, medicinal species were indicated for 49 diseases, which were grouped into 15 categories of body systems. Conclusion . This study shows the presented divergence in relation to their therapeutic use; in this point, these divergences reinforce the importance of pharmacological research.